Sistem Pendukung Keputusan Kelayakan Nasabah Kredit Pada Koperasi Simpan Pinjam Menggunakan Metode Scoring System - Dewi Rosida (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2022)
The feasibility of applying for credit is one of the requirements that must be passed by a customer before being able to apply for credit. This is very important because to avoid bad credit. But efforts to minimize the risks that arise are still very small, lack of accuracy and inaccurate decision making, a customer often makes mistakes in analyzing. Processes that are too long also often make time ineffective and inefficient. The customer will be determined whether or not he is eligible to get credit at the Artha Putra Mandiri Jember Cooperative after fulfilling several conditions set by the cooperative with the BPKB (motorcycle / car) as collateral. The method to be used is the scoring system method. The results of this study are that the system can provide the right recommendations for a customer in making a decision whether a customer applying for credit has the eligibility to be approved or rejected for a credit application.